(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Sediments from freshwater bodies of the Northern Guinea Savanna Zone of Nigeria act as reservoirs for mineral and chemical nutrients washed from different sources around the environment. This research aimed at assessing the chemical and macronutrients of the sediments from freshwater bodies and the geomorphology of the area. A global positioning system, Model N9 GARMIN eTrexLegend™, personal navigator® was used to determine the geomorphological features while a polyvinyl chloride tube of 1.0 m long, 25 mm in diameter and 2.0 mm thick was used for sediment collection from a depth of 0-15 cm. The result of the chemical properties of the sediment; pH, organic carbon, organic matter and total nitrogen were found to be higher in dry season whereas phosphorus was high in the rainy season and there was no variation in the macronutrient across the dry and rainy season. Sand had the highest percentage across both seasons for particle distribution. This study revealed that sediments are rich in macronutrients and can be employed for agricultural purposes.